Enhancing English Language Learning: A Case Study of SMPN 3 Bathin - Saleha, Dinda Qoneta; Reski, Bekri (LPPM STMIK Dharmapala Riau, 2024)
The purpose of this case study is to evaluate the students at SMPN 3 Bathin Solapan's English learning capabilities. Through a detailed analysis of teaching methods, obstacles faced, and student reactions, the study explores the application of English language instruction. The principal technique of gathering data was interviewing Mr. Ardhy Yalvema S.Pd., an experienced English teacher at the school, who shared thoughts about the efficacy of existing instructional methodologies and his own teaching approaches. In the context of SMPN 3 Bathin Solapan, the study's findings help to clarify the variables affecting students' capacity to learn English.